A Comparison of the Fading of Dyestuffs as Textile Colourants and Lake Pigments - Jo Kirby; David Saunders (Heritage)
Dyed wool samples and lake pigments prepared from the same dyestuffs were exposed to light over the course of 14 months. Brazilwood or sappanwood, cochineal, madder, and weld were used for both wools and pigments, with the addition of dyer’s broom, indigo, and tannin-containing black dyes for the wools and eosin for the pigments. The wools were dyed within the MODHT European project on historic tapestries (2002–2005), using recipes derived from fifteenth- to seventeenth-century sources. The pigments were prepared according to European recipes of the same period, or using late nineteenth-century French or English recipes. Colour measurements made throughout the experiment allowed for overall colour difference (ΔE00) to be tracked and half-lives to be calculated for some of the colour changes. Alterations in the samples’ hue and chroma were also monitored, and spectral information was collected. The results showed that, for both textiles and pigments, madder is the most stable red dye, followed by cochineal, and then brazilwood. Eosin was the most fugitive sample examined. Comparisons of textile and lake samples derived from the same dyestuff, whether red or yellow, indicate that the colourants are more stable when used as textile dyes than in analogous lake pigments.